Cross-cultural adaptation and psychometric properties of the Chinese version of the postpartum depression literacy scale - Guo, Pingping; Cui, Nianqi; Mao, Minna; Zhang, Xuehui; Chen, Dandan; Xu, Ping; Wang, Xiaojuan; Zhang, Wei; Zheng, Qiong; Zhang, Le; Xiang, Zhenzhen; Jin, Yin; et al. (Frontiers in Psychology, 2022)
Background and Aim: The postpartum depression literacy (PoDLi) of perinatal women is closely related to the occurrence, recognition, and treatment of postpartum depression, therefore valid instruments for evaluating the level of PoDLi are of great significance for both research and clinical practice. This study aimed to cross-culturally adapt the postpartum depression literacy scale (PoDLiS) into Chinese and to test its psychometric properties among Chinese perinatal women. Methods: A cross-sectional study was conducted from April to May 2022 in a tertiary hospital in Hangzhou, Zhejiang Province, China. 619 out of the 650 perinatal women that were approached via a convenience sampling method completed the Chinese version of the PoDLiS (C-PoDLiS). Content validity (the content validity index of items (I-CVI) and scale-level content validity index (S-CVI)) was evaluated by an expert panel. Psychometric properties, including item analysis, structure validity (exploratory factor analysis, confirmatory factor analysis), convergent and discriminant validity, reliability (internal consistency, test-retest reliability), criterion validity (concurrent validity, predictive validity), and floor/ceiling effect were examined. Results: The final version of C-PoDLiS is a six-factor structure consisting of 27 items, which explained 61.00% of the total variance. Adequate content validity (I-CVI=0.833-1.00, S-CVI=0.920) was ensured by the expert panel. The modified confirmatory factor analysis model revealed that the 6-factor model fitted the data well (χ2/df=1.532, root mean square error of approximation=0.042, goodness of fit=0.900, incremental fit index=0.949, comparative fit index=0.948, Tucker-Lewis index=0.940). The total Cronbach's α was 0.862, the total McDonald’s ω was 0.869, and the test-retest reliability coefficient was 0.856. Results of convergent validity (average variance extracted = 0.486-0.722) and discriminant validity provided good or acceptable psychometric support. Significant correlations between scores of the C-PoDLiS and Mental health literacy scale (r = 0.155-0.581, p < 0.01) and Attitudes toward seeking professional psychological help short form scale (r=0.361-0.432, p < 0.01) supported good concurrent and predictive validity, respectively. No floor/ceiling effect was found. Conclusion: The C-PoDLiS was demonstrated to be a sound instrument with good reliability and validity for evaluating Chinese perinatal women’s PoDLi levels. Its use in the future can facilitate data aggregation and outcome comparisons across different studies on this topic.